Trophic discrimination factor and the significance of mangrove litter to benthic detritivorous gastropod, Ellobium aurisjudae (Linnaeus) - Teoh, Hong Wooi; Sasekumar, A.; Ismail, Mohamad Hanif; Chong, Ving Ching (Elsevier, 2018)
In stable isotope analysis, the estimation of proportional contribution of carbon and nitrogen from mangrove to benthic invertebrates requires knowledge of the food-consumer trophic discrimination factor (∆ δ13C and ∆ δ15N). This study tested the hypothesis that the mangrove gastropod Ellobium aurisjudae can assimilate low quality refractory mangrove litter and aimed to determine the trophic discrimination values (TDV) of C and N isotopes between gastropod and the mangrove producer. The mean ∆ δ13C for gastropods fed senescent leaves of the mangrove Bruguiera parviflora (Roxb) Wight & Arn and decomposing mangrove (unknown species from the same site) wood were estimated at 5.3 ± 0.3‰ and 3.2 ± 0.5‰ respectively, whereas for ∆ δ15N, these values were 4.2 ± 0.2‰ and 6.0 ± 0.2‰ respectively. The gastropod assimilated refractory carbon from mangrove leaf and wood litter with 49% and 18% efficiency respectively. Rearing experiment of gastropods (n = 25) fed only mangrove wood litter over 5months in the laboratory, showed mean weight increments of 14.8–74.4% depending on the initial animal weight. Significant deviation of the TDVs for E. aurisjudae from the generalized discrimination values for herbivory underscores the need to use specific TDV for the detritivory link.